2018
DOI: 10.1158/1538-7445.am2018-5477
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5477: Targeting nicotinamide phosphoribosyltransferase (NAMPT) with OT-82 in Ewing sarcoma

Abstract: EWS is an aggressive malignancy affecting adolescents and young adults, for which novel therapies are critically needed. Recent insights have revealed that NAMPT is a potential therapeutic target, mediating the rate limiting step of the NAD salvage pathway which converts nicotinamide (NAM) to nicotinamide mononucleotide (NMN). This pathway is preferentially utilized in tumor cells where it is essential for maintaining cellular bioenergetics and provides the necessary substrate for NAD-dependent proteins. OT-82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…OT-82 enhances the efficacy of other drugs, such as cytarabine and dasatinib. Studies in mice and nonhuman primates indicated that OT-82 was well tolerated and showed no cardiac, neurological, or retinal toxicity [ 205 , 206 , 207 ].…”
Section: Nad/nampt Axis In Cancermentioning
confidence: 99%
“…OT-82 enhances the efficacy of other drugs, such as cytarabine and dasatinib. Studies in mice and nonhuman primates indicated that OT-82 was well tolerated and showed no cardiac, neurological, or retinal toxicity [ 205 , 206 , 207 ].…”
Section: Nad/nampt Axis In Cancermentioning
confidence: 99%
“…For iNAMPT specific small molecules inhibitors exist, most known FK866 (also known as APO866) and GMX1778 (also known as CHS-828), among others (Table 1) (139143, 159–161). However, most of the data on these drugs describe their effect on the tumor itself, and not on cells of the microenvironment (141, 161).…”
Section: Nampt In Metabolic Regulation and Activation Of Myeloid Cellsmentioning
confidence: 99%